Service science for socio-economical and information systems advancement holistic methodologies - Koumpis, Adamantios, 1969-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Services both as a science and as a practice in today's corporate environments are suffering from many suboptimalities. A compromise of both organizational and technological aspects provides the answer to many pitfalls and shortcomings currently faced. This book sheds light on a variety of issues and shortcomings of service-based economies by analyzing situations and modern practices that improve the way researchers, field practitioners, and ICT professionals account for their core business service-related activities. This defining body of research provides a broad perspective of how to improve service creation, production, and management of assets.
Service science and practice -- About the nature of services -- Typology of services -- Services and the humans -- Services and the computers -- Services and the workplace -- Service economics -- Service physics -- Service metaphysics -- Culture of services -- Future of services.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 19, 2010).
Keywords: Service industries; Information technology; Corporate culture; Carambola approach; Collaborative environment; Collaborative versus competitive paradigm; Dilemma service; Nature of services; Service analysis model; Service conceptualization; Service science; Service synthesis; Supply chain management; Typology; Electronic books